ANTROPOLOGICAL APPROACHES IN LEGAL CERTAINTY RESEARCH - H. Z. Ogneviuk (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Purpose. The study is aimed at highlighting in the historical-comparative context the influence of anthropological teachings on the development and formation of such a legal phenomenon as "legal certainty", proving that the category of legal certainty appeared as a consequence of anthropocentric philosophical approach in law. Theoretical basis. In the article, using the system approach, the content of the term "legal certainty" was analyzed. The axiological approach allowed generalizing various manifestations of legal certainty within the limits of one va-lue concept and generalizing it by formulating and emphasizing the importance of the anthropophilosophical approach in the study of legal phenomena. The method of comparison, analysis, synthesis, generalization of philosophical concepts was used, in which the principle of legal certainty was expressed in different periods of historical development. Originality. This article supports a wide approach to understanding the principle of legal certainty, and the latter one relates to general theoretical legal principles. It is alleged that legal certainty consists of a number of requirements for lawmaking and law enforcement. In conducting a historical analysis for these requirements of legal certainty, it was established that they were historically originated and developed as a part of anthropological philosophical doctrine and subsequently embodied in law. The connection with anthropological teaching in jurisprudence is transformed into a relationship between the realization of the principle of legal certainty and human rights. Conclusions. Anthropological approaches in the study of legal phenomena allow providing value humanistic orientation to law. Human rights and freedoms as the most important social value require observance of them even when the legislation is imperfect, uncoordinated, contains gaps and uncertainties. The principle of legal certainty enables to overcome these difficulties, due to it the requirements of lawfulness and observance of human rights and freedoms are agreed upon. This principle is generally legal, and its content is revealed through a set of components – requirements.